Performance changes and relationship between vertical jump measures and actual sprint performance in elite sprinters with visual impairment throughout a Parapan American games training season - Loturco, Irineu; Winckler, Ciro; Kobal, Ronaldo; Cal Abad, Cesar C.; Kitamura, Katia; Veríssimo, Amaury W.; Pereira, Lucas A.; Nakamura, Fábio Y. (Frontiers in Physiology, 2015)
The aims of this study were to estimate the magnitude of variability and progression in actual competitive and field vertical jump test performances in elite Paralympic sprinters with visual impairment in the year leading up to the 2015 Parapan American Games, and to investigate the relationships between loaded and unloaded vertical jumping test results and actual competitive sprinting performance. Fifteen Brazilian Paralympic sprinters with visual impairment attended seven official competitions (four national, two international and the Parapan American Games 2015) between April 2014 and August 2015, in the 100- and 200-m dash. In addition, they were tested in five different periods using loaded (mean propulsive power [MPP] in jump squat [JS] exercise) and unloaded (squat jump [SJ] height) vertical jumps within the 3 weeks immediately prior to the main competitions. The smallest important effect on performances was calculated as half of the within-athlete race-to-race (or test-to-test) variability and a multiple regression analysis was performed to predict the 100- and 200-m dash performances using the vertical jump test results. Competitive performance was enhanced during the Parapan American Games in comparison to the previous competition averages, overcoming the smallest worthwhile enhancement in both the 100- (0.9%) and 200-m dash (1.43%). In addition, The SJ and JS explained 66% of the performance variance in the competitive results. This study showed that vertical jump tests, in loaded and unloaded conditions, could be good predictors of the athletes’ sprinting performance, and that during the Parapan American Games the Brazilian team reached its peak competitive performance.